The Impact on Economic and Environmental Development of COVID-19 Pandemic: a Case Study in Indonesia - Nur Indriani Dewi; Fadilla Citra Melati (Ekuilibrium : Jurnal Ilmiah Bidang Ilmu Ekonomi, 2021)
The goal of this analysis is to examine in greater detail the effect of the COVID-19 pandemic on economic development and the quality of the atmosphere in Indonesia. This report uses secondary data as the primary source, obtained using a secondary data collection method from many different organizations. Different government policies and measures to discourage the escalation of the transmission of the Coronavirus, one of which is large-scale social restrictions (PSBB). However, before Indonesia suffered a recession, the PSBB actually became a barrier to economic development. As a part of this program, the rise in environmental efficiency is another positive effect because traffic that generates emissions and vast manufacturing sectors that create dirty waste is temporarily halted. Based on the findings of the review, this report notes that there is a detrimental effect of COVID-19 on economic development in Indonesia. However, because of the introduction of PSBB, Indonesia's air quality has improved. This report is intended to serve as a reference and assessment of the effects of COVID-19 on the economy and the atmosphere for stakeholders and the general public. In order to allow the government to consider measures that will deter the spread of the coronavirus and restore the economy without damaging improved air quality.